Tumor‐Microenvironment‐Responsive Cascade Reactions by a Cobalt‐Single‐Atom Nanozyme for Synergistic Nanocatalytic Chemotherapy. Issue 48 (2nd September 2022) - Cai, Shuangfei; Liu, Jiaming; Ding, Jianwei; Fu, Zhao; Li, Haolin; Xiong, Youlin; Lian, Zheng; Yang, Rong; Chen, Chunying
Abstract: Nanocatalytic therapy, involving the nanozyme‐triggered production of reactive oxygen species (ROS) in the tumor microenvironment (TME), has demonstrated potential in tumor therapy, but nanozymes still face challenges of activity and specificity that compromise the therapeutic efficacy. Herein, we report a strategy based on a single‐atom nanozyme to initiate cascade enzymatic reactions in the TME for tumor‐specific treatment. The cobalt‐single‐atom nanozyme, with Co−N coordination on N‐doped porous carbon (Co‐SAs@NC), displays catalase‐like activity that decomposes cellular endogenous H2 O2 to produce O2, and subsequent oxidase‐like activity that converts O2 into cytotoxic superoxide radicals to efficiently kill tumor cells. By incorporation with doxorubicin, the therapy achieves a significantly enhanced antitumor effect in vivo. Our findings show that cascade TME‐specific catalytic therapy combined with chemotherapy is a promising strategy for efficient tumor therapy. Abstract : A cobalt‐single‐atom nanozyme, with Co−N coordination on N‐doped porous carbon (Co‐SAs@NC), displayed tumor‐microenvironment‐responsive cascade enzymatic activities with both catalase‐ and oxidase‐like properties, specifically generating cytotoxic superoxide radicals from overexpressed H2 O2 . The nanocatalytic therapy led to a remarkably enhanced antitumor effect in vivo by further integration with doxorubicin.